An Empirical Study on the Factors Influencing the Number of Fans of Female-Oriented Accounts on Chinese Tik Tok - Du, Yanyan; Lin, Shengliang; Zhang, Xueli (Frontiers in Psychology, 2022)
This paper selects 500 samples through a recommendation algorithm, and on the basis of content analysis, examines the factors that affect the number of fans of female-oriented accounts on Chinese Tik Tok in terms of intrinsic attributes, surface form and deep content. The results show that in order to increase the number of fans of female-oriented accounts on Chinese Tik Tok, there are 4 variables of the intrinsic attribute with statistically significant differences, 13 variables of the surface form with statistically significant differences and 9 variables of the deep content with statistically significant differences. Beauty-related content is not the best means to attract fans. It requires Tik Tok creators to get rid of stereotyped and conceptual female impressions, display the rich social roles of women, and build true, complete and harmonious female images in innovative ways in accordance with the humanistic communication concept.